2010
DOI: 10.37546/jaltjj32.1-1
|View full text |Cite
|
Sign up to set email alerts
|

Attributions for Performance: A Comparative Study of Japanese and Thai University Students

Abstract: Attribution theory posits that people look for causes for their successes and failures. Past research indicates that these causal attributions may influence future performance, and it has been suggested that attributional tendencies may be affected by culture and outcome. To understand the role that culture and outcome may play in attributions for foreign language learning, a set of questionnaires was designed to investigate how EFL university students (355 Thai and 350 Japanese) in two countries judged their … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
14
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 37 publications
5
14
0
Order By: Relevance
“…This finding suggests that when learning ESL, the students depended highly on situation or environment. This study is also in line with Mori et al (2010) where they found out that the Japanese and Thai university students focused more on external factors for success such as teacher's encouragement and classroom atmosphere; enjoyment of the lesson and getting good grades. Teacher, class and task belong together as the most influential external attributions to achievement.…”
Section: Resultssupporting
confidence: 86%
“…This finding suggests that when learning ESL, the students depended highly on situation or environment. This study is also in line with Mori et al (2010) where they found out that the Japanese and Thai university students focused more on external factors for success such as teacher's encouragement and classroom atmosphere; enjoyment of the lesson and getting good grades. Teacher, class and task belong together as the most influential external attributions to achievement.…”
Section: Resultssupporting
confidence: 86%
“…Locus of causality dimension correlates with students' perception of their success and failure due to their external or internal factor. Individuals with an internal locus of causality for their success (e.g., ability, effort) tend to show greater pride when achieving this success compared to those that attribute externally (e.g., luck, complex tasks) (Mori, Gobel, Thepsiri & Pojanapunya, 2010;Santrock, 2011).…”
Section: Rositomentioning
confidence: 99%
“…Thus, when they refer failure to stable factors (e.g., bad luck, lack of effort), they would also expect failure in the future. Likewise, these individuals develop their expectation that they would be successful in the future because they perceive that failure could be changed (Santrock, 2011;Mori et al, 2010).…”
Section: Rositomentioning
confidence: 99%
See 2 more Smart Citations